Letter (copy) : International conference on Spain' - Tewson, Vincent
021-0042-001 HVT/EK/608. Secretary's. 31st March, 1937. Mr. J. Thomas, Barry and District Trades Union Council, 8, Claude Road, Barry, GLAM. Dear Mr. Thomas, INTERNATIONAL CONFERENCE ON SPAIN. I have your letter of the 24th March and quite appreciate the feelings of your Council owing to the varied reports which have appeared in the Press of what was purported to have been said by British representatives at the International Conference held on March 10th and 11th. As a matter of fact, Mr. Bevin and Mr. Attlee spoke on behalf and at the request of a fairly large British delegation and were not expressing mere personal views. There has been a good deal of misrepresentation in certain quarters. The Conference was one of many which have been held on this subject under the auspices of the International Federation of Trade Unions and the Labour and Socialist International. No reports have been issued in connection with previous meetings and we understand that there is no intention of doing so in the case of the last Conference. Under these circumstances I am unable to assist you in the request you make. Yours sincerely, Assistant Secretary. 292/946/21/42